Second Level Password Generator - Tay, Choo Chuan; Sakidin, Hamzah; Herman, Nanna Suryana; Baharon, Mohd Rizuan (2010)
Password gives user access to the university computing services. Every time the user connects, he or she must provide the magic word; he must prove he is who he says he is. The intruder with the necessary knowledge, experience, and tools gains entry to a system, he or she may be able to monitor other machines and systems on the same network and capture information about local users logging on to those machines. And if these users then connect to other networks, the intruder has the potential to penetrate and monitor the remote systems to which the local users connect, thereby increasing the likelihood of a breach in the security of those systems as well. Therefore, it is important to have a second level security to the user's password. Cryptography is an art to convert a message into other forms by using some algorithms. It is used widely in many fields such as securing message before sending through email, sending confidential documents or letters through networks, doing business online and etc. The two algorithms chosen to develop this system are Advanced Encryption Standard (AES) and Data Encryption Standard (DES). The purpose of choosing AES and DES is because they are two of the most popular algorithms for modern encryption.